English language in professional training of higher education seekers in specialty 193 "Geodesy and Land Surveying": today's challenges - Maniutina, O.; Bespalko, R.; Hutsul, T. (Land Management, Cadastre and Land Monitoring, 2023)
An overview and application of the English language in the world at the modern stage were conducted. The key importance of the English language for international business and scientific communication was clarified. The prerequisites for the use of the English language in Ukraine and its legislative support at the current stage were considered. The content and scope of the discipline "Professional foreign language" in the training program for specialists in specialty 193 "Geodesy and land surveying" were determined. The cycle "education – science – production" regarding the use of the English language in the specified specialty was analyzed.At the education stage, the need to achieve the B2 level is substantiated both for the possibility of barrier-free implementation of international academic mobility during studies, and for the possibility of its continuation at the following educational and qualification levels of higher education (master's degree, doctor of philosophy). The scientific stage reveals the terminological problems and the importance of working with professional specialized literature for the formation of publishing activity and other criteria related to the knowledge of a foreign language, necessary for obtaining academic degrees. The production moment examines the English language through the prism of working with technical and technological support necessary for carrying out topographic-geodetic, cartographic and land-cadastral works.Keywords: English language, geodesy, globalization, European integration, land surveying, international academic mobility, education.
Keywords: English language; geodesy; globalization; European integration; land surveying; international academic mobility; education.